2020
DOI: 10.24996/ijs.2020.61.8.6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Effects of Lemon Peel -Silver Nanoparticles Versus Brand Toothpastes and Mouthwashes on Staphylococcus Spp. Isolated From Teeth Caries

Abstract: Thirty one  samples of gum swabs were collected from patients with tooth caries (5-30 years old)  from the College of Science (Biology department )- University of Baghdad- Iraq for the period from October 2018 to December 2018. , The samples were transported, after inoculation in a transport media (nutrient broth), to the laboratory of the College of Science and then cultured on mannitol salt agar and  blood agar). The isolates belonging to Staphylococcus spp. were identified by biochemical tests and Vitek 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Next, NPs synthesis is assessed by change of color by the solution The nally obtain powder by air dried and kept in dry place for further characterization [9]. The use bacteria to synthesizes nanomaterials with the development antimicrobials with in vitro activities against pathogenic bacteria [10] Characterization of CuO NPs Characterization is the core tool for successful applications and the understanding of nanoparticles. The following methods were used to determine NPs characteristics: SEM and TEM are used to characterize the shapes and sizes.…”
Section: Synthesis Of Cuo Npsmentioning
confidence: 99%
“…Next, NPs synthesis is assessed by change of color by the solution The nally obtain powder by air dried and kept in dry place for further characterization [9]. The use bacteria to synthesizes nanomaterials with the development antimicrobials with in vitro activities against pathogenic bacteria [10] Characterization of CuO NPs Characterization is the core tool for successful applications and the understanding of nanoparticles. The following methods were used to determine NPs characteristics: SEM and TEM are used to characterize the shapes and sizes.…”
Section: Synthesis Of Cuo Npsmentioning
confidence: 99%
“…Streptococcus mutans is colonized on the oral surfaces and constitute more than 75% of the cultivated bacteria that existed in the human dental plaque that leads to dental caries and may cause teeth loss in children and adults [2]. Antimicrobial activity of several compounds was tested against clinical isolates including streptococcus mutans collected from patients suffering from different dental diseases in Iraq [3]- [5]. Furthermore, mechanisms of actions of secondary metabolites are reviewed as the causative factors responsible for the antimicrobial activity of plants against streptococcus mutans clinical isolates [6], also Leuconostoc mesenteroides biofilm may be used as an antimicrobial agent [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the antibiotic susceptibility test coincided with those of [27], who reported that S. aureus was resistant to Ciprofloxacin (54.2%) and Gentamicin (12.5%). According to [28], 37% and 29% are resistant to Ciprofloxacin and Gentamycin, respectively, while according to [29] and [30], VRE clones, or vancomycin-resistant enterococci, are becoming a global public health concern. At this time, the only treatment available for Enterococcus-related infections that are resistant to ampicillin and aminoglycoside antibiotics is glycopeptide antibiotics.…”
Section: Histopathologymentioning
confidence: 99%